Ensuring Security in Indonesia's Digital Landscape using Electronic Signature Validation: Menjamin Keamanan dalam Lanskap Digital Indonesia menggunakan Validasi Tanda Tangan Elektronik - Santoso, Elga Dwiky; Purwaningsih, Sri Budi (Indonesian Journal of Law and Economics Review, 2024)
Abstract: Digital technology enhances communication and transactions, but unauthorized document modifications necessitate secure electronic signatures due to the risk of unauthorized modifications. This research aims to identify electronic signatures compliant with the ITE Law in Indonesia to ensure their legal validity and enforceability. By utilizing a normative research method with a statute approach, this study examines primary sources, including Law No. 11 of 2008 on Electronic Information and Transactions, Ministerial Regulation No. 11 of 2008 on Electronic Certification, and Law No. 71 of 2019 on Electronic Systems and Transactions. The results indicate that electronic signatures must fulfill specific criteria outlined in Article 11 of the ITE Law to be considered legally binding. These criteria require that the data used for the electronic signature is solely associated with the signer and under their control at all times, along with mechanisms to track modifications and identify signers' approval. The novelty of this research lies in its comparative analysis of certified versus non-certified electronic signatures, contributing to a deeper understanding of their legal implications. The implications of this study highlight the necessity for enhanced authentication measures to safeguard the integrity of electronic transactions, ultimately promoting confidence in digital communications and transactions in Indonesia. Highlights: Electronic signatures improve security in digital transactions. Compliance with ITE Law ensures legal validity. Valid signatures require data control and modification tracking. Keywords: Electronic Signatures, ITE Law, Legal Validity, Digital Transactions, Indonesia